The relationship between Spirulina platensis and selected biomechanical indicators of tibiae in rats - Bayram Suzer; Nilay Seyidoglu; Kenan Tufekci; Sevda Inan (Veterinární Medicína, 2020)
There are several dietary supplements, particularly herbal foods, that have been used in an attempt to improve bone growth. In this study, we aim at determining the effects of low- and high-doses of Spirulina platensis, a "Superfood", on the bone growth and biomechanical indicators. Thirty Wistar rats, weighing 250 g, at the age of 7-8 weeks were assigned to three groups: The Control group (basal diet), Low-dose group (LDG; 500 mg/kg) and High-dose group (HDG; 1 000 mg/kg) of S. platensis. S. platensis was given daily by oral gavage in a 45-day-trial. At the end of the study, the right tibiae were collected and subjected to bone biomechanical tests (bone weight, bone length, maximum load, stiffness, breaking deflection, fracture toughness, post-yield displacement and yield load). Serum samples were also analysed for the calcium and phosphorus concentrations. There were significant increases in bone weight, bone length, maximum load, breaking deflection, work to fracture, post-yield displacement and yield load (P = 0.025, P = 0.019, P = 0.030, P = 0.015, P = 0.031, P = 0.028, P = 0.049, respectively), whereas stiffness non-significantly increased. However, there were no significant differences (P > 0.05) for any variables between the LDG and the HDG. Although the serum phosphorus concentrations showed no differences among any of the groups, the serum calcium concentration increased significantly in LDG compared to Control group (P = 0.009; 7.14 ± 0.47 and 9.45 ± 0.67, respectively). However, no differences were observed in HDG in terms of serum calcium. In conclusion, S. platensis had positive effects on the bone growth and biomechanical bone features. Therefore, our study supports the use of S. platensis as an alternative food additive for bone growth and health in growing animals.